Recent progressive developments in conductive-fillers based polymer nanocomposites (CFPNC's) and conducting polymeric nanocomposites (CPNC's) for multifaceted sensing applications - Shubham Sharma; Akarsh Verma; Sanjay Mavinkere Rangappa; Suchart Siengchin; Shigenobu Ogata (Journal of Materials Research and Technology, 2023)
Conducting polymer nanocomposites (CPNC's) are promising materials for sensor devices possessing design pliability, good sensitivity, and low temperature operation. For producing conducting polymer nanocomposites with tunable morphology, the soft template procedure is one of the advantageous aspects as reported from in-depth literature. Since the diameter and aspect ratio of conducting-polymer nanomaterials have affected the charge-transport properties, hence, the fine tuning of their structures is important to enhance sensitivity. This review has focused on the CPNC's membranes, insulative-polymers with conductive-fillers based CPNC's (IPCFCPNC's) and conductive-fillers based polymer nanocomposites (CFPNC's) which have been incorporated in many prior literary sources including the usage of strain sensors in some sensing applications for detection pressure, gas humidity, etc. As the review sheds light on incorporating specific types of nanofillers, such as graphene or carbon nanotubes or conducting filling-agents, into the CPNC's membrane matrix and insulative-polymeric-matrices, it will be possible to improve their mechanical stability, enabling them to be used for high-performance sensing applications. In addition, the review has evident that by using advanced fabrication techniques, such as electrospinning, it is possible to create thin, flexible CPNC's membranes that exhibit high sensitivity and stability towards target analytes. Therefore, the feasibility of CPNC's, IPCFCPNC's, and CFPNC's in sensor applications has thoroughly been reviewed for the purpose to realize the novel flexible CPNC structures and their other aspects of applications that may cater to new horizons in high-end smart flexible sensing applications. Additionally, the advanced discovery is to combine conductivity measurement and rheology analysis using a new emerging class of CPNC's, IPCFCPNC's, and CFPNC's for remarkable electrical properties. It is highly appealing to find out more about novel CPNC's, IPCFCPNC's, and CFPNC's, and their role in sensor matrices, considering their unique properties. Based on conducting polymers (CPs), and insulative-polymers with conductive filling-agents that have been reported during the past forty years, the properties and performance of sensing matrices have been investigated by incorporating the diverse carbon-based nano-additives and other nano filling-agents. Furthermore, another area of interest is the use of CPCs, and insulative-polymers with conductive filling-agents for the development of bio-sensors. CPCs, and insulative-polymers with conductive filling-agents can be functionalized with biological molecules such as enzymes, antibodies, and nucleic acids, to create highly sensitive sensors for the detection of various biological markers, including glucose, lactate, and pH. Along with myriads of illustrations in accordance with the CPs and their composites with nanoparticles, carbon materials, or conductive filling-agents with insulative-polymeric-matrices etc., their salient characteristics have been enumerated in this comprehensive review. Additionally, CPNC's, IPCFCPNC's, and CFPNC's-sensing devices will have to improve their analytical performance for a widespread spectrum of multifaceted sensing applications in future research trends.